ADI-270: an armored allogeneic gamma delta T cell therapy designed to target CD70-expressing solid and hematologic malignancies - Jie Zhang; Jyothi Sethuraman; Marissa Herrman; Pranav Murthy; Ramandeep Kaur; Jonathan T S Wong; Kevin P Nishimoto; Smitha R Y Gundurao; Arun Bhat; Blake T Aftab; Shon Green; Aruna Azameera; et al. (Journal for ImmunoTherapy of Cancer)
Background The tumor microenvironment (TME) poses challenges that limit the efficacy of conventional CAR-T cell therapies. Homing barriers, immunosuppressive factors, and target antigen heterogeneity can impair CAR-T cell functional activity within the TME. Alternative strategies have contemplated incorporating the use of gamma delta (γδ) T cells as a CAR-T cell approach to potentially overcome these limitations. γδ T cells possess both innate and adaptive immunity to facilitate broad tumor recognition, and their natural propensity for tissue tropism may allow for more effective tumor infiltration. Reported here is the preclinical characterization of ADI-270, an allogeneic γδ CAR-T cell product targeting CD70+ cancers, engineered with a third-generation CAR based on the natural CD27 receptor. ADI-270 is also double-armored to mitigate the immunosuppressive effects of TGFβ and reduce the potential for allogeneic rejection.Methods Vδ1 T cells engineered to express an anti-CD70 CAR and dominant negative TGFβ receptor II (dnTGFβRII) were expanded from healthy donor human PBMCs. The phenotype and functional characterization of ADI-270 were assessed with in vitro cell culture assays and in vivo tumor xenograft models.Results ADI-270 exhibited high levels of in vitro cytotoxicity against a panel of cancer cell lines and displayed a favorable inflammatory cytokine profile compared with reference scFv-based anti-CD70 CAR αβ T cells. Cytotoxicity remained potent despite low CD70 expression observed in multiple solid and hematologic tumor cell models. When armored with dnTGFβRII, ADI-270 exhibited functional resilience to TGFβ-mediated inhibition of T cell effector activity. In addition, the incorporation of potent and sensitive CD70-targeting decreased T cell-mediated alloreactive killing against ADI-270 in vitro without evidence of fratricide. Finally, ADI-270 displayed robust tumor tropism and control of primary and secondary tumor challenges in xenograft mouse models.Conclusions These results demonstrate the robust potency and capacity of ADI-270 to extend antitumor activity to cancers with heterogeneous antigen expression. The functional armoring incorporated into ADI-270 provides a mechanism to overcome the limitations of reduced efficacy and persistence within the TME. ADI-270 has the potential to target multiple CD70+ cancers with initial clinical evaluation proceeding in relapsed/refractory clear cell renal cell carcinoma.Trial registration number NCT06480565.